Pembelajaran Ekplorasi Mendalam dan Pemecahan Kreatif; Studi Desain Pembelajaran Berbasis Bahtsul Masa’il - Muhammad Sirojuddin; Achmad Jalilul Chakam; Asep Saepul Hamdani; Irma Soraya (Program Pascasarjana Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This article reveals the urgency of educators to continue to pay attention to the right learning design to find out the presentation according to the needs and learning characteristics of each student. One of the appropriate alternative learning models for use by educators is Bahtsul Masa'il-based learning design. This model engages students to participate in learning activities and helps them learn how to utilize time, become more independent in learning, and learn to think critically. This model tends to demand that students actively conduct investigations in solving problems so that they learn to use their logic. In fact, in-depth exploration of building lifelong learning skills, independence in gaining knowledge, and creative ways to utilize existing resources. There are seven steps that must be taken to apply the learning of Bahtsul Masa'il in his practical life. This study used a descriptive qualitative approach. The source of the data was taken from field observations and interviews of several Asatidz at the Assalafi Al Fithrah Islamic boarding school in Surabaya and students who were activist of the yellow book at the Ulya and Wustho levels. The analysis uses triangulation analysis techniques. Furthermore, based on the research analysis